DISTRIBUSI MOLEKULER SPESIES HETEROATOM DALAM MINYAK BATUBARA INDONESIA - Murti, Sri Djangkung Sumbogo; Yusnitati, Yusnitati (Badan Pengkajian dan Penerapan Teknologi, 2010)
Heteroatom-containing species in the coal liquid oils (CLO) were identified andquantified by the aid of gas chromatography with atomic emission detector (GCAED).Four different CLOs from different rank coals, processes and cut pointswere investigated in the present study. Thiophene and its derivatives were foundto be the major sulfur compounds, pyridines and anilines, and phenols were themajor nitrogen and oxygen compounds, respectively in the oils of boiling range 300oC). An oil of boiling range (300?420oC) carried moredimethyldibenzothiophenes and benzoquinolines. The correlation between feedcoal and liquid product was discussed in terms of the compositions ofheteroatomic compounds.Kata kunci: coal liquid oil, heteroatomic compounds, GC-AED